Change of trace elements content in sewage water under the influence of hydrophilic macrophytes; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Akhmed-Ogly K. V. (Hydrogeochemistry and Hydrogeoecology, 2014)
Title screen